ECONOMICAL AND LEGAL CONTROL OF TURNOVER OF RESULTS OF INTELLECTUAL ACTIVITY OF RUSSIAN INDUSTRIAL ENTERPRISES - Dmitriy A. Lovtsov; Marina V. Bogdanova (Статистика и экономика)
The article considers valid principles, primary tasks, most importance factors and conditions (limitations), perspective system model and actual mechanisms of effective economic-legal control of intellectual work results turnover of Russian industrial enterprises.